2016
DOI: 10.1057/ejdr.2015.33
|View full text |Cite
|
Sign up to set email alerts
|

Linkages with Multinationals and Domestic Firm Performance: The Role of Assistance for Local Firms

Abstract: This article uses firm-level data for 19 African countries to look at the link between domestic firms' business relationship with multinationals and their performance in terms of innovation and productivity. Quite uniquely, we also evaluate the importance of support received by the domestic firm, either from the government or the multinational business partner, for this link. Overall, our data analysis shows that for the average domestic firm, supplying to a foreign multinational in the country is positively a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 36 publications
1
21
0
4
Order By: Relevance
“…The FDI spillover impact on local suppliers is high knowledge transfer because foreign companies set up a certain level of quality standards on raw materials from local suppliers (Marlevede et al 2014). Foreign companies provide technical and managerial training to their suppliers (Gorg & Seric 2016). The empirical studies those indicated an impact of FDI on suppliers are Liang (2017), Suyanto et al (2014), Wang & Wong (2016).…”
mentioning
confidence: 99%
“…The FDI spillover impact on local suppliers is high knowledge transfer because foreign companies set up a certain level of quality standards on raw materials from local suppliers (Marlevede et al 2014). Foreign companies provide technical and managerial training to their suppliers (Gorg & Seric 2016). The empirical studies those indicated an impact of FDI on suppliers are Liang (2017), Suyanto et al (2014), Wang & Wong (2016).…”
mentioning
confidence: 99%
“…Also, we can see a similar result in the strong positive inclination of annual employment growth (the change in fulltime employment reported in the current fiscal year from a previous period) (Figure 1-d). Such developments are well confirmed in established literature that deals with effect from foreign direct investments (Egger et al, 2001;Javorcik, 2015;Görg and Seric, 2016). When it comes to capacity utilization based on comparison of the current output with the maximum output possible using the current inputs by firms, it can be said that there is no evidence to claim for certain a negative outcome.…”
Section: Results On Productivitymentioning
confidence: 80%
“…Spillovers can be spawned through the movement of labor between vertically related industries using their skills acquired in a foreign firm for the purposes of a local one or creating spin-offs on their own. Nevertheless, this is all dependent on the level of integration of domestic firms into supply chains of foreign direct investments (Caves, 2007;Görg and Seric, 2016). Generally, foreign firms source internationally limiting the variety of the inputs produced in a local economy.…”
Section: Positive Effectsmentioning
confidence: 99%
“…Overall, 2,113 foreign‐owned firms participated in the survey. The data has been used for former analysis of FDI in Africa (e.g, Amendolagine et al ; Görg and Seric ), but not yet with a focus on CSR. More details on the Africa Investor Survey 2010, the sampling procedure and quality assurance measures are provided in UNIDO ().…”
Section: Designmentioning
confidence: 99%